Adaptive-integration-time image sensor with real-time reconstruction function. - Yasuda, T.
A computational image sensor is proposed in which the pixel controls its integration time to light intensity. The integration time of each pixel is selected from among several lengths of integration time and the integration time is shortened if the pixel intensity becomes saturated. Although the integration time of each pixel varies, the pixel intensity is adjusted on the sensor in real time. The dynamic range of the pixel value output from the proposed sensor is greatly widened. A prototype of 64×48 pixels has been fabricated by using 2-poly 2-metal 0.8-μm CMOS process. The proposed sensor has simple functions for the comparison of intermediate integration value and threshold to control the integration time and nonlinear image reconstruction. Because the maximum number of the comparison-reset operations during a frame is three, one of the four integration times can be selected pixel by pixel. The circuit and layout design of the prototype which has computational elements based on column parallel architecture are described and the fundamental functions have been verified. By the experiments, it has been verified that the sensor can achieve a wide dynamic range by adapting to light.
Keywords: 0.8 micron; 2-poly 2-metal CMOS process; 3072 pixel; 48 pixel; 64 pixel; Adaptive-integration-time image sensor; Circuit design; Column parallel architecture; Comparison-reset operations; Computational image sensor; Dynamic range; Layout design; Light intensity; Nonlinear image reconstruction; Real-time reconstruction function